ANALISIS PELANGGARAN KODE ETIK DALAM KASUS PEMBERHENTIAN KETUA MK ANWAR USMAN TERKAIT PUTUSAN BATAS USIA CAPRES DAN CAWAPRES PADA PEMILU 2024 - Cantika Dhea Marshanda Zulqarnain; Nararya Salsabila Zamri; Raesa Mahardika (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
This Essay analyzes the violation of the code of ethics in the case of the dismissal of the former Chief Justice of the Constitutional Court, Anwar Usman, regarding the decision in case 90/PUU-XXI/2023 regarding the age limit for presidential and vice presidential candidates in the upcoming 2024 election. This decision caused controversy because it was considered biased and favored certain parties who were related to the judge in deciding the case. The judge was then proven guilty of violating 5 codes of ethics, namely the principles of impartiality, integrity, skill and thoroughness, independence and appropriateness and decency, which resulted in Anwar Usman's dismissal as chairman of the Constitutional Court. The article is prepared in a qualitative descriptive manner using a literature study method which aims to outline the analysis of violations committed by Anwar Usman and their impact on the credibility and integrity of the Constitutional Court as a law enforcement institution. There are several findings in the form of clear evidence of violations of the code of ethics and behavior of judges by Anwar Usman, namely a lack of sensitivity to issues of conflict of interest, suboptimal judicial leadership affecting his neutrality as a constitutional judge and the intervention of external parties in the decision-making process which threatens the independence of the Constitutional Court. So the author formulates the need for the establishment of a permanent internal supervisory apparatus in order to have broader authority in correcting problematic decisions and increasing proactive nature in preventing violations of the judge's code of ethics.